Rationale and methods of an observational study to support the design of a nationwide surgical registry: the MIDAS study - Werner Vach; Franziska Saxer; Anders Holsgaard-Larsen; Søren Overgaard; Erik Farin-Glattacker; Nicolas Bless; Heiner C. Bucher; Marcel Jakob (Swiss Medical Weekly, 2018)
BACKGROUND